Children who chase lost voices [videorecording (DVD)] - Shinkai, Makoto; Kanemoto, Hisako; Inoue, Kazuhiko, 1954-; Irino, Miyu, 1988-; Hartzog, Corey; Matranga, David (Sentai Filmworks, 2012)
When she hears a strange song from a crystal radio, Asuna is transported to a mysterious world where mythical beasts roam and brave warriors fight for their lives. Agartha is a land of breathtaking beauty and unimaginable danger--a place where it is believed even the dead can be brought back to life. But at what cost?